2011
DOI: 10.1007/s11556-011-0085-x
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being in European countries—on the age-specific impact of physical activity

Abstract: As an attempt to measure the 'experienced' utility of individuals in economics, the investigation of individuals' subjective well-being (SWB) was pioneered by Van Praag and Frijters (1999) and Kahneman et al. (1999). Since then, a number of studies has analysed the factors associated with SWB and policy makers are now recognising the importance of SWB as a policy target, with the implication being that one could target its factors associated with increase in the overall SWB in countries. However, despite its s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 35 publications
8
55
1
6
Order By: Relevance
“…Social participation is also significantly related to life satisfaction, in line with what was revealed in earlier studies (Putnam 2000;Helliwell and Putnam 2005;Pawlowski et al 2011) and the hypothesis H3. In particular, the results from multilevel analysis indicate that this positive association between social participation and life satisfaction changes along with household income.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Social participation is also significantly related to life satisfaction, in line with what was revealed in earlier studies (Putnam 2000;Helliwell and Putnam 2005;Pawlowski et al 2011) and the hypothesis H3. In particular, the results from multilevel analysis indicate that this positive association between social participation and life satisfaction changes along with household income.…”
Section: Discussionsupporting
confidence: 90%
“…The correlation between participation in social activities and life satisfaction is well evidenced (e.g., Lim and Putnam 2010;Putnam 2000;Helliwell and Putnam 2005). Studies have found that the frequencies of attending social events, including team sports, eating out and participating in religious activities are associated with life satisfaction and community cohesion (Lee and Park 2010;Leyden et al 2011;Lim and Putnam 2010;Pawlowski et al 2011;Rasciute and Downward 2010). For instance, Leyden et al (2011) find that chances of participating in voluntary activities and access to cultural and leisure facilities are positively related to happiness.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For example, people who report higher levels of happiness undertake more physical activity (e.g. Pawlowski, Downward, & Rasciute, 2011), report more moderate levels of alcohol and smoking involvement (e.g. Piper, Kenford, Fiore, & Baker, 2012) and increased social connections (Kok et al, 2013).…”
Section: The Importance Of Being Happymentioning
confidence: 99%
“…Sport participation itself can lead to benefits in physical (Humphreys, MacLeod, & Ruseski, 2011) and mental health Pawlowski, Downward, & Rasciute, 2011;Rasciute & Downward, 2010). According to Preuß et al (2012), over 20% of the German population only participates in sports between three times a month and once a year.…”
Section: Implications and Limitationsmentioning
confidence: 99%